White Pass and Yukon Railroad locomotive 109 - Swanberg, J.W. (Jack W.), 1939- (Photographer) (1977)
Locomotive on train 6 to Skagway, Alaska, in Bennett, British Columbia, Canada Archives & Special Collections, University of Connecticut Library J. W. Swanberg Papers